(untitled) (Global Scientific Review, 2023)
100 pieces of nuts of different sizes grown in local areas were selected. The nut was separated from the nut shell in its entire position and the nut dimensions were measured in diameter on the long side. A mathematical statistical analysis was carried out in order to determine the range of the main dimensions of the measured oars. This article presents the work and results of mathematical statistical analysis. The purpose of determining the core size range of the core is to base the size of the sieve hole, which is the working part of the sorting machine.